Comprehensive metagenomic insights into a unique mass gathering and bathing event reveals transient influence on a riverine ecosystem - Yadav, Rakeshkumar; Rajput, Vinay; Gohil, Kushal; Khairnar, Krishna; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
The religious mass gathering and bathing can pose a multitude of significant public health challenges and lead to severe alterations in the river microbial ecology. The Pandharpur Wari is an annual pilgrimage of Maharashtra, India, where millions of devotees carry the footprints of the saint-poets and pay their obeisance to Lord Vitthal on the 11th day of moon's waxing phase (Ashadi Ekadashi). As a part of the ritual, the engrossed devotees, walk over 250 km, take a first holy dip in a sacred river Indrayani at Alandi and secondly in Bhima River at Pandharpur. The MinION-based shotgun metagenomic approach was employed to examine the impact of spiritual mass bathing on environmental changes (concerning the river microbial community structure and functions); and public health aspects (in terms of changes in the pathogenic potential and antibiotic resistance). The analysis of bathing and post-bathing samples of both the rivers revealed alterations in the alpha and beta diversity, indicating significant spatiotemporal variations in the overall microbial structure and function. Furthermore, the analysis revealed up to 80% of differences in the abundance of virulence genes between the bathing and post bathing samples. We observed parallel increase of priority skin and enteric pathogens (ranging from 11% to 80%) such as Acinetobacter baumannii, Staphylococcus aureus, Streptococcus pyogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa during the bathing event. Moreover, we observed a significant increase in the antibiotic resistance in the bathing samples of Bhima and Indrayani rivers respectively. Altogether, this is the first comprehensive metagenomic study unravelling the influence of religious mass-bathing on the riverine ecosystem.
Keywords: Antibiotic resistance; Mass bathing; MinION sequencing; Priority pathogens; Virulence genes

Characterization of a novel Tequatrovirus phage from pristine stretch of the Ganges River, India, in reducing bacterial load from sewage water - Samson, Rachel; Pawar, Ameya; Khairnar, Krishna; Dharne, Mahesh (Journal of Environmental Chemical Engineering, 2025)
Effective treatment of wastewater (WW) and its reuse is necessary to meet certain sustainable development goals and a circular economy. Escherichia coli is one of the primary contaminants in the WW, and its extra-intestinal occurrence poses a considerable threat under one health. This study is the first report of a novel broadspectrum phage (& fcy;ERS-1) isolated from a pristine stretch of the Ganges River in the biocontrol of E. coli, resistant to 3rd-and 4th generation cephalosporins and aztreonam. This is the first report of a phage from the Tequatrovirus genus to infect P. aeruginosa. The & fcy;ERS-1 could reduce the abundance of E. coli cells by 8.22 log10 CFU/mL <= 24 hrs. Additionally, phi ERS-1 disrupted the biofilm of E. coli with a reduction of 3.88 log10 CFU/mL. Further, phi ERS-1 could inhibit biofilm by multiple strains of E. coli (ATCC 8739, 25922, 43888) and multiple generaincluding E. coli ATCC 8739, Shigella boydii ATCC 9207, P. aeruginosa (ATCC 9027). The phage phi ERS-1 reduced bacterial counts in raw WW by 2 log10 CFU/mL and 4 log10 CFU/mL reduction in coliform-enriched WW in <= 24 hours. Overall, this study suggests that phi ERS-1 could be used as an effective alternative to be combined with other treatments for improving the quality of WW disposal and environmental health by reducing the bacterial load.
Keywords: Antibiofouling; Biofilm; Coliform; Ganges; Green approach; Phages; wastewater